Borrowed from your grandchildren : the evolution of 100-year family enterprises - Jaffe, Dennis T. (John Wiley & Sons, Inc., 2020)
"Many families believe that creating wealth is the real achievement; after that everything is easy. But that is far from the case: most family wealth runs into difficulty as the family attempts to pass it to the next generation and have them use it wisely. Sustaining and even adding to the family wealth across generations is actually a greater challenge than making it. The media is full of tragedies and morality tales about the loss of family wealth over generations, and how wealth produces successive generations of heirs who are dysfunctional and unproductive. Families search for advisors who can help them overcome this. But a few well-known families do not rest after their first generation of success. They continue to succeed across generations and develop new generations of family leaders who use their wealth in wise and wonderful ways, and even add to the family "wealth" both financially as well as in human and social dimensions. These family dynasties are role models for many families who want to see their wealth have positive impact on their children, as well as family employees and their community. This book presents the accumulated wisdom from a group of nearly 100 large global families who have continued as partners in business and wealth management over three of more generations. They are called Generative Families because they generate rather than diminish their wealth. Reporting from a study that interviewed 100 large, global families who had sustained a successful business and family connection over more than three generations. A picture is presented--in their own words--of the nature of global family enterprises and how they evolve over generations. These families are very private and do not commonly share the full details of what they have done to sustain vitality across generations. After a successful first generation, these families focus on developing a great family and renewing the business --engaging across generations, developing clear and collaborative governance for family and business, developing the next generation, and serving the wider community"--